2015
DOI: 10.3998/ark.5550190.p009.191
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of diospongin A, ent-diospongin A and C-5 epimer of diospongin B from tri-O-acetyl-D-glucal

Abstract: We describe a new synthesis of diospogin A, its enantiomer ent-diospongin A and C-5 epimer of diospongin B from commercially available tri-O-acetyl-D-glucal, based on a copper catalyzed Michael addition of phenyllitium to the corresponding ,-unsaturated ketone. The stereochemical course of the Michael addition was unambiguously established by X-ray crystallographic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…3,4,6-tri-O-acetyl-D-glucal (17) has been used as a cheap starting material for the synthesis of biologically active Diospongin A (38) and ent-diospongin (34) natural products by Fall and co-workers (Scheme 4). [17] Initially glucal17 is converted to α, β-unsaturated ketone 29 via three steps which subsequently undergo the copper-catalyzed Michael addition of phenyl lithium to give a separable mixture of diastereomeric ketones 30 and 31 in a 1 : 1 : 2 ratio. Stereoselective reduction of compounds 30 and 31 followed by the subsequent side chain elaboration led to desired compounds ent-diospongin A (34) and diospongin A (38) respectively in good yields.…”
Section: Drmohd Saleem Was Born and Raised In The Rajouri District Of...mentioning
confidence: 99%
See 2 more Smart Citations
“…3,4,6-tri-O-acetyl-D-glucal (17) has been used as a cheap starting material for the synthesis of biologically active Diospongin A (38) and ent-diospongin (34) natural products by Fall and co-workers (Scheme 4). [17] Initially glucal17 is converted to α, β-unsaturated ketone 29 via three steps which subsequently undergo the copper-catalyzed Michael addition of phenyl lithium to give a separable mixture of diastereomeric ketones 30 and 31 in a 1 : 1 : 2 ratio. Stereoselective reduction of compounds 30 and 31 followed by the subsequent side chain elaboration led to desired compounds ent-diospongin A (34) and diospongin A (38) respectively in good yields.…”
Section: Drmohd Saleem Was Born and Raised In The Rajouri District Of...mentioning
confidence: 99%
“…Pieter et al reported [31] , the synthesis of the papulacandin D derivatives which is differing by acid side chain group from Papulacandin D. Initially they synthesized anomeric activated glucal derivative (90) from tri-O-acetyl D-glucal (17). The aglycon moiety (81) in Papulacandin D was synthesized by using 3, and 5-hydroxy benzoic acid.…”
Section: Drmohd Saleem Was Born and Raised In The Rajouri District Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of (–)-diospogin A ( 1 ) and ent -diospongin A ( 3 ) was demonstrated by Fall et al from tri - O -acetyl- d -glucal, by using copper-catalysed Michael addition of phenyllitium. 27 Initially, compound 92 was synthesized from 91 in two steps. Next, 92 was subjected to PDC-mediated oxidation to form α,β-unsaturated ketone 93 followed by copper-catalysed Michael addition of PhLi, to give diastereomeric ketones 94a and 94b .…”
Section: Synthesis Of Chiral Diosponginsmentioning
confidence: 99%
“…The synthesis of (-)-diospogin A (1) and ent-diospongin A (3) was demonstrated by Fall et al from tri-O-acetyl-Dglucal, by using copper-catalysed Michael addition of phenyllitium. 27 Initially, compound 92 was synthesized from 91 in two steps. Next, 92 was subjected to PDC-mediated oxidation to form ,-unsaturated ketone 93 followed by copper-catalysed Michael addition of PhLi, to give diastereomeric ketones 94a and 94b.…”
Section: Fall's Approach (2015)mentioning
confidence: 99%